Preferensi Politik Pada Pemilihan Kepala Desa - Muhammad Arsad Nasution, Ihwan Sormin & Fatahuddin Aziz Siregar & (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2020)
This study aims to determine what the people's political preferences are in the election of the Head of Huta Baru Village, Huta Baru District, South Tapanulli Regency. The formulation of the problem raised in this study is whether the community's political preferences in the election of the Head of Huta Baru Village, Kuantan Tengah District, Kuantan Singingi Regency.The data collection technique used is in the form of a questionnaire, namely a list of questions where the respondent just chooses the answers that the researcher has provided. The samples taken in this study were 100 people from the Huta Baru Village community.To test the correctness of the research, researchers used descriptive-qualitative data analysis techniques. Descriptive-Qualitative, namely analyzing the data obtained based on reality and then linked with a theory that supports the discussion, so that it can explain the causes and effects that affect political participation in the village. This descriptive analysis begins with data collection, data presentation, data analysis and finally drawing conclusions. The indicators in this study are the presence of stimuli, someone's characteristics, social care and high social status.The results of the study proved that the stimulant indicator was more dominant as a political preference in the election of the Head of Huta Baru Village, Batang Toru District, South Tapanuli Regency.